Frequency Invariant Beam Steering for Short-Pulse Systems with a Rotman Lens - Andreas Lambrecht; Piotr Laskowski; Stefan Beer; Thomas Zwick (International Journal of Antennas and Propagation)
A promising approach for beam steering of high-voltage transient signals for HPEM-systems (High Power Electro Magnetic) is presented. The inherent capability of the Rotman lens to provide true time delays is used to develop a prototype beam steering device for an antielectronics HPEM system in the frequency range from 350 MHz to 5 GHz. Results of analytical calculations, simulations, and measurements from a hardware prototype are presented. The detailed mechanical setup of the Rotman lens is presented. Additionally the output pulses are investigated when inputting a Gaussian-like transient signal. Then time domain measures of quality (full width at half maximum, ringing, delay spread, maximum of transfer function) are investigated for these output transients, and the simulation and measurement results are compared. A concluding analysis of the realizable time domain array pattern shows the radiated pulse form.